Das Evangelium nach Matthäus - Konradt, Matthias (Das Neue Testament Deutsch, 2023)
In this very concise compendium Matthias Konradt presents a theologically oriented commentary of the first Gospel in the Bible. This is an ideal commentary for preparing sermons and for work in the parish. In this very concise compendium Matthias Konradt presents a theologically oriented commentary of the first Gospel in the Bible. The Introduction consists of 20 pages that include the most important pieces of information concerning recent research on the literary background, on the historical origins, on the historical context and on the theological peculiarities of the Gospel of Matthew. An ideal commentary for preparing sermons and for doing parish work.
Gesehen am 16.11.2023
Keywords: Kommentar; Bibel / Matthäusevangelium